HUBUNGAN PENGGUNAAN GIGI TIRUAN DENGAN STATUS GIZI, ASUPAN ZAT GIZI MAKRO DAN KECUKUPAN SERAT PADA LANJUT USIA DI KELURAHAN LIMO - Zazkia Azzahra, (2021)
As you get older, the greater your susceptibility to tooth loss. Tooth loss can affect speech function and psychological aspects, namely aesthetics, tooth loss can also reduce chewing function and affect nutritional intake so that it will affect general health conditions and a person's quality of life. To improve mastication, the elderly mostly use dentures. This study aims to the relationship between the use of dentures with nutritional status, intake of macronutrients and fiber adequacy in the elderly in Limo Village. This study is an observational analytic with cross sectional design. The populations were all elderly who live in Limo Village, taking samples using purposive sampling method as many as 60 elderly. Data analysis using chi-square test. The results showed that there was a significant relationship between the use of dentures with nutritional status (p value = 0,000), energy intake (p value = 0,000), protein intake (p value = 0,000), fat intake (p value = 0.024) and carbohydrate intake. (p value = 0.001) and there is no significant relationship between the use of dentures and the adequacy of fiber in the elderly in Limo Village (p value = 0.542). it is expected that the elderly will continue to maintain nutritional intake in order to improve the nutritional status independently both in denture users or not.